Impact of National Scheme For Liberation and Rehabilitation (Nslrs) on Occupational and Economic Status of Scavengers: a Case of Haryana: Assessing the Impact of NSLRS on Scavengers' Occupational and Economic Status in Urban Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Present study was carried out in urban Haryana to knowthe occupational and   economic status ofscavengers in Haryana after implementation of the National Scheme ForLiberation And Rehabilitation of Scavengers (NSLRS).  The total sample of 415 respondents   was selected from Ambala, Kurukshetra,Karnal, Panipat, Sonipat district of Haryana.  The list of the respondents was prepared with the help of the listpublished by   Scheduled CastesDevelopment Financial Corporation (SCDFC) Haryana.  The respondents, as reflected in our sample,exhibit certain characteristics that are peculiar to their degradation andbackwardness in their occupational and economic status. As far as therespondents in our sample are concerned there are three basic elements thatdetermine the economic position of the family: 1. the condition and type ofhouses, 2. their income and 3. Occupation. Results shows that   larger percentage of the respondents 56.1%have Brick/stone wall+Tiled Roof type of houses and  64.1% have the size of two roomsand separate kitchen and bathroom and majority of the respondents(51.1%) have annual income up to Rs. 50000/- per annum and maximum people  are  engaged in the work of  sweeping/cleaningoccupation (63.9%) .  The difference between past and present   occupation shows that only 5.7% respondentleft their traditional occupation i.e. sweeping /scavenging after theimplementation of this scheme.